A6.20 Ectopic lymphoid neogenesis is strongly associated with activation of the IL-23 pathway in rheumatoid synovitis. (13th February 2015) - Yeremenko, N; Celis, R; Blijdorp, I; Ramírez, J; Pablos, JL; Sanmartí, R; Cañete, JD; Baeten, DL
Abstract : Background and objectives: The functional relevance of synovial ectopic lymphoid neogenesis (ELN) in rheumatoid arthritis (RA) remains unknown. As ELN correlates with the degree of tissue inflammation we investigated whether ELN was associated with specific cytokine profiles. Materials and methods: Paired synovial tissue (ST) (n = 63) and fluid (SF) (n = 44) was obtained from the inflamed knee joints of RA patients. Synovial inflammation and ELN was determined by immunohistology. CD21L was used as molecular marker of ELN. Cytokine expression was determined by ELISA and quantitative PCR in SF and ST, respectively. Results: 48% of ST displayed ELN by histology. ELN+ samples had increased T and B lymphocyte infiltration (p < 0.001) and CD21L expression (p = 0.014). SF analysis showed higher expression of IL-23 (p = 0.018) and IL-17F (p = 0.028) in ELN+ versus ELN- samples, with a similar trend for IL-22 (p = 0.070). Other cytokines, including IL-17A, IL-6, TNF-a, Th1 cytokines and Th2 cytokines, were not different. In ST, IL-23 (p = 0.030) mRNA levels were increased in ELN+ samples. Moreover, CD21L expression as molecular marker of ELN correlated significantly with mRNA expression of IL-23 (r = 0.70), IL-17F (r = 0.42), IL-21 (r = 0.30) and IL-22 (r = 0.33), but not IL-17A. The strong correlation between CD21L and IL-23, IL-17F, IL-21 end IL-22 was confirmed in an independent RA ST sample set (n = 36). IFNg and IL-2, but not IL-6 and TNF-α, also showed some correlation with CD21L expression. Conclusion: Synovial ELN in RA is strongly associated with increased expression of IL-23/IL-17-related cytokines. Whether patients depicting synovial ELN respond differently to therapeutic targeting of this pathway remains to be determined.